Centenarians—the way to healthy vascular ageing and longevity: a review from VascAgeNet - Sabrina Summer; Maria Borrell-Pages; Rosa-Maria Bruno; Rachel E. Climie; Konstantina Dipla; Aysenur Dogan; Kseniia Eruslanova; Emil Fraenkel; Francesco Mattace-Raso; Christopher J. A. Pugh; Keith D. Rochfort; Mark Ross; et al. (GeroScience, 2024)
The prevalence of centenarians, people who lived 100 years and longer, is steadily growing in the last decades. This exceptional longevity is based on multifaceted processes influenced by a combination of intrinsic and extrinsic factors such as sex, (epi-)genetic factors, gut microbiota, cellular metabolism, exposure to oxidative stress, immune status, cardiovascular risk factors, environmental factors, and lifestyle behavior. Epidemiologically, the incidence rate of cardiovascular diseases is reduced in healthy centenarians along with late onset of age-related diseases compared with the general aged population. Understanding the mechanisms that affect vascular ageing in centenarians and the underlying factors could offer valuable insights for developing strategies to improve overall healthy life span in the elderly. This review discusses these key factors influencing vascular ageing and how their modulation could foster healthy longevity.